DAMPAK PERUSAHAAN KELAPA SAWIT TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT (Studi Kasus PT. Prima Mitrajaya Mandiri di Desa Loleng Kecamatan Kota Bangun Kabupaten Kutai Kartanegara) (The Impact of Oil Palm Company on Social Economic Condition of Community (Case Study PT. Prima Mitrajaya Mandiri in Loleng Village Kota Bangun Subdistrict Kutai Kartanegara District)) - ULVA NUR HIDAYAH; NIKE WIDURI; SYARIFAH MARYAM (Universitas Mulawarman (University of Mulawarman), 2020)
The establishment of oil palm companies let impact on society. The purpose of this study was to know the social and economic impact of the establishment of oil palm company on the community. This research was conducted from May to July 2019 in Loleng Village, Kota Bangun District, Kutai Kartanegara District. Oil palm company exists in there namely PT. Prima Mitrajaya Mandiri. Number of respondents was as many as 44 respondents divided into two parts, namely 22 respondents are residing close to the company and 22 respondents are living far away from the company. The method of data analysis that used was descriptive analysis. The research results showed that oil palm company let positive impact on the community who live near to the company. The establishment of company opens employment opportunities, increases people's living standards, and opens business opportunities. The company gives many help for community lives near the company such as financial assistance to orphans, school repair assistance, and road repair assistance. People who live far away from the company did not have the positive impact.